Distinct leaf water potential regulation of tree species and vegetation types across the Cerrado–Amazonia transition - Soares Jancoski, Halina; Schwantes Marimon, Beatriz; C. Scalon, Marina; de V. Barros, Fernanda; Marimon‐Junior, Ben Hur; Carvalho, Eder; S. Oliveira, Rafael; Oliveras Menor, Imma (Biotropica, 2022)
The Cerrado–Amazonia transition harbors forest and savanna formations under the influence of pronounced climate seasonality; however, the water use strategies of this key region is not yet well understood. This study aimed at deciphering in intra‐ and interspecific variability in leaf water potential regulation among species across three distinct vegetation types (typical cerrado, cerradão, and semideciduous seasonal forest) of the Cerrado–Amazonia transition region. We expected a variation across iso/anisohydric strategies driven by plant–environment interactions and by species attributes (phenology and wood density). We selected 21 dominant species (seven per vegetation type), recorded their phenological strategy and wood density, and measured leaf water potential (Ψl) during the dry and rainy seasons to analyze variations associated with minimum Ψl, predawn Ψl (ΔΨpd), and midday Ψl (ΔΨmd) under the effect of variable vapor pressure deficit (VPD). The variation in Ψl across species was higher in the dry season than in the rainy season for all vegetation types. Most species from typical cerrado and cerradão showed similar behavior patterns, with higher Ψl regulation under high VPD and lower ΔΨpd. In contrast, most forest species showed lower regulation under high VPD, and higher ΔΨpd. Total or partial deciduousness together with strong stomatal regulation seems to be common water regulation strategies in the dry season for cerrado species but not for forest species. Our results suggest that, if drought events become more intense and frequent as predicted, seasonal forest species may be more vulnerable due to their lower Ψl regulation. in Portuguese is available with online material. Resumo A transição Cerrado‐Amazônia abriga formações florestais e savânicas sob a influência de acentuada sazonalidade climática; no entanto, as estratégias de uso da água nesta região chave ainda não são bem compreendidas. Este estudo visa decifrar a variabilidade intra e interespecífica na regulação do potencial hídrico foliar entre as espécies em três fitosocionamias (cerrado típico, cerradão e floresta estacional semidecidual) da região de transição Cerrado‐Amazônia. Esperávamos uma variação nas estratégias iso / anisoídricas por causa das interações planta‐ambiente, bem como pelos atributos das espécies (fenologia e densidade da madeira). Selecionamos 21 espécies dominantes (sete por fitofisionomia), registramos sua estratégia fenológica e densidade da madeira, e medimos o potencial hídrico foliar (Ψl) durante as estações seca e chuvosa para analisar as variações associadas ao Ψl mínimo, Ψl ao amanhecer (ΔΨpd) e ao meio‐dia Ψl (ΔΨmd) sob o efeito do déficit de pressão de vapor (VPD). A variação de Ψl entre as espécies foi maior na estação seca do que na estação chuvosa para todos os tipos de vegetação. A maioria das espécies de cerradão e cerradão típico apresentaram padrões de comportamento semelhantes, com maior regulação Ψl sob alta VPD e menor ΔΨpd. Em contraste, a maioria das espécies florestais apresentou menor regulação sob alto VPD e maior ΔΨpd. Desfolhamento total ou parcial junto com forte regulação estomática parecem ser estratégias comuns de regulação da água na estação seca para espécies de cerrado, mas não para espécies florestais. Nossos resultados sugerem que, se os eventos de seca se tornarem mais intensos e frequentes como previsto, as espécies florestais sazonais podem ser mais vulneráveis devido à sua regulação de Ψl mais baixa. Our article finds that dominant species from a tall woodland savanna have similar leaf water potential regulation than savanna species and different than forest species at the Amazonia–Cerrado transition.